Influence of calcium channel antagonist on the pharmacodynamics of a second-generation sulfonylurea in rats and rabbits - Murthy, T E Gopala Krishna; Mayuren, C (Asian Journal of Pharmaceutics (AJP), 2014)
Diabetes mellitus is a chronic metabolic disorder characterized by elevated blood glucose concentration known as hyperglycemia. Diabetes mellitus covers a wide range of heterogeneous diseases and involves management of its associated acute and chronic complications; thus, there is every possibility of administering other drugs along with the primary anti-diabetic agent, which may be the cause for a drug-drug interaction to occur. In the present study, the possible pharmacodynamic interaction was studied with amlodipine besylate and gliclazide in diabetic rats and healthy rabbits. The animals were divided into three groups. Gliclazide was studied at a dose of 1.44 mg/200 g and 5.6 mg/1.5 kg body weight in rats and rabbits respectively. Amlodipine besylate at a dose of 0.090 mg/200 g and 0.350 mg/1.5 kg body weight was used for the interaction study in rats and rabbits respectively. The drugs were administered orally and the blood samples were collected before and after administration of drug for a period of 16 h in rats and 24 h in rabbits. The serum samples were then subjected to glucose estimation by glucose peroxides method. The percentage reduction in blood glucose levels were calculated with respect to initial levels. Gliclazide showed a significant reduction of elevated and normal blood glucose levels. The extent of blood glucose reduction was comparatively reduced in the case of combination therapy of amlodipine besylate and gliclazide. The study also suggests the necessity to readjust the dose of gliclazide when co-administered with amlodipine besylate.